ORIENTASI PEMAHAMAN MUNÂSABAH DALAM QS. AL-QIYAMAH PERSPEKTIF ABDULLAH DARRÂZ DI MA’HAD AL-QUR’AN UNIVERSITAS PTIQ JAKARTA - Hamdani Anwar; Asep Muksin; Ahmad Thib Raya; Bunga Ifatun Nisa; Ahmad Zain Sarnoto; Raudhatul Husna (MADANI Abdimas : Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
The method of analyzing the structure of the Qur'anic text has been offered by many scholars, both classical scholars and contemporary scholars. One of them is Abdullah Darrâz in his book An-Nabâu Al-Azhîmu Nazharâtun Jadîdatun fî Al-Qur'ân. The purpose of this study is to try to analyze how Abdullah Darrâz's munasabah thought in analyzing the interrelationships of the verses in the Qur'an. This paper finds that Abdullah Darrâz's munâsabah thought can be used in analyzing the coherence of each arrangement of the verses of the Qur'an in a letter by first determining the introduction (muqaddimah), the main objective (maqâsid), and finally finding the conclusion al-Qur'an (Al-Khâtimah) from a chapter of the Qur'an